Kant’s Aesthetic Theory - Kemal, S. author. aut Link
XI, 197 p.
Keywords: This authoritative and accessible book explains the argument and strategy of Kant's analysis of beauty. A number of issues are discussed - amongst them the distinction and relation between natural beauty and fine art, pure and dependent beauty, disinterestedness and universality, form and expression, beauty and morality, transcendental and empirical necessity, individual and community. Links are also forged between Kant's theory and contemporary commentaries - including those by Donald Crawford, Jacques Derrida, Paul Guyer, Rudolph Makkreel, Mary McCloskey, Kenneth Rogerson and John Zammito.